Minimaly Invasive Transforaminal Lumbar Interbody Fusion Surgery at Level L5-S1 - Daniel S. Fidalgo (2019)
There are various techniques to obtain lumbar interbody fusion (LIF) at L5-S1 functional unit (FSU) level. This paper presents a finite element analysis to investigate the biomechanical changes caused by transforaminal lumbar interbody fusion (TLIF) at the L5-S1 FSU level. The information collected can be used to choose the best chirurgical treatment to solve several pathologies. This approach places the implant into the anterior portion of the intervertebral disc space, which stabilizes the flexion-extension movement across the operated level. Numerical results of segmental motion show that torsion and extension load cases yield the highest rotation angles during the early and long-term postoperative phases, respectively. Furthermore, a decrease in autogenous bone graft volume results in a reduction of displacements and rotation angles.